Violation of the principle of justice during investigations (مجلة أبحاث قانونية, 2023)
Justice has always been blind and an abstract entity, not biased except for the party of the right, as it reflects the path of the authorities authorized to investigate the extent of its application of the provisions of the law, and it rarely tends to considerations of the public interest in some issues, especially the political related to the public affairs of society, in the event that it is necessary to violate The provisions of the law, and since the philosophy of justice has many considerations, the bulk of which is based on the birth of values ​​and pillars from which it is not permissible to deviate, which impose on the authorities and law enforcement men to apply them relentlessly, which makes it a goal intended by all legislation and laws.
Keywords: principle of justice; investigations